Effects of la-dopant on phase, microstructure and dielectric properties of Bi4Ti3O12 ceramics - Siriprapa P. (2014)
Bi4-xLaxTi3O12 (where x = 0, 0.25, 0.50, 0.75 and 1) powders and ceramics were prepared using conventional solid state reaction and sintering procedures. The calcination was carried out at 750 °C for 4 h and sintering was done at 1150 °C for 4 h. The density of all ceramics was found to be comparable regardless of La concentration. X-ray diffraction analysis showed that preferred orientation of ceramic grains was reduced with addition of La ions. This reduced preferred orientation was accompanied by a decrease in grain size. The temperature dependence of dielectric constant showed a decrease in Tc with increasing La concentration. © (2010) Trans Tech Publications.